Environmental factors and financial performance: Evidence from the Indian cement industry - Kulkarni, G Srinivas; Belavadi, Nikhil (International Journal of Management and Sustainability, 2025)
This investigation explores the influence of environmental determinants on corporate performance within the Indian framework, concentrating specifically on the cement industry, an area frequently neglected in the literature pertaining to Environmental, Social, and Governance (ESG) despite its considerable ecological impact. Although there has been a proliferation of global research on sustainability, a deficiency of targeted and definitive evidence persists, especially in emerging markets such as India. To address this, our study used data from 2013 to 2022 from 15 prominent cement firms listed on the National Stock Exchange (NSE), utilizing secondary data acquired from the Bloomberg database and Smart PLS as analysis tools. We applied Structural Equation Modelling (SEM) in conjunction with a bootstrapping method consisting of 5,000 resamples. The examination demonstrates that environmental performance metrics exert a significantly negative effect on corporate performance. Furthermore, capital expenditure reveals a negative indirect influence on enterprise valuation. Environmental disclosures positively affect enterprise value when mediated by sales performance, suggesting that transparency regarding sustainability efforts can bolster both reputation and financial gain. The findings are based on Indian cement firms, underscoring the imperative of integrating sustainable practices into corporate strategic planning.